THE EFFECT OF PERCEIVED OF USEFULNESS, EASY TO USE, EXPERIENCE TO ATTITUDE USER GOJEK ON GOPAY - Parulian Parulian; Monika Budiman (SEAN Institute, 2023)
Gojek is a technology company that offers transportation services, food delivery, and numerous other services via mobile applications. Gopay is a financial service offered by Gojek that enables Gojek application users to conduct transactions. This study aimed to determine how expediency, experience, and convenience influence the attitudes of gojek users towards gopay. This study's participants are all Gojek users in Bekasi. Regarding the technique used to determine the sample, the researcher employed a technique of purposive sampling with a sample size of 68. The sampling was conducted by distributing a Googleform to gojek users who utilize gopay. Analysis of data using the smartPLS program. The results of the study indicate that the attitude of gojek users toward gopay is affected by expediency, experience, and convenience. Gopay has numerous advantages for users in terms of usability. Many users are satisfied with Gopay because the transaction process is quick and straightforward. Gopay provides its users with unique conveniences.